Anisotropy and inhomogeneity of permeability and fibrous network response in the pars intermedia of the human lateral meniscus. (November 2021) - Berni, Matteo; Marchiori, Gregorio; Cassiolas, Giorgio; Grassi, Alberto; Zaffagnini, Stefano; Fini, Milena; Lopomo, Nicola Francesco; Maglio, Melania
Abstract: Within the human tibiofemoral joint, meniscus plays a key role due to its peculiar time-dependent mechanical characteristics, inhomogeneous structure and compositional features. To better understand the pathophysiological mechanisms underlying this essential component, it is mandatory to analyze in depth the relationship between its structure and the function it performs in the joint. Accordingly, the aim of this study was to evaluate the behavior of both solid and fluid phases of human meniscus in response to compressive loads, by integrating mechanical assessment and histological analysis. Cubic specimens were harvested from seven knee lateral menisci, specifically from anterior horn, pars intermedia and posterior horn; unconfined compressive tests were then performed according to three main loading directions (i.e., radial, circumferential and vertical). Fibril modulus, matrix modulus and hydraulic permeability of the tissue were thence estimated through a fibril-network-reinforced biphasic model. Tissue porosity and collagen fibers arrangement were assessed through histology for each region and related to the loading directions adopted during mechanical tests. Regional and strain-dependent constitutive parameters were finally proposed for the human lateral meniscus, suggesting an isotropic behavior of both the horns, and a transversely isotropic response of the pars intermedia. Furthermore, the histological findings supported the evidences highlighted by the compressive tests. Indeed, this study provided novel insights concerning the functional behavior of human menisci by integrating mechanical and histological characterizations and thus highlighting the key role of this component in knee contact mechanics and presenting fundamental information that can be used in the development of tissue-engineered substitutes. Statement of significance: This work presents an integration to the approaches currently used to model the mechanical behavior of the meniscal tissue. This study assessed in detail the regional and directional contributions of both the meniscal solid and fluid phases during compressive response, providing also complementary histological evidence. Within this updated perspective, both knee computational modeling and meniscal tissue engineering can be improved to have an effective impact on the clinical practice. Graphical abstract: Image, graphical abstract